Isolation, Genomic Analysis, and Preliminary Application of a Bovine Klebsiella pneumoniae Bacteriophage vB_Kpn_B01 - Luo, Zidan; Geng, Shangjingchao; Lu, Biao; Han, Guangli; Wang, Yin; Luo, Yan; Yang, Zexiao; Cao, Suizhong; Yao, Xueping (Frontiers in Veterinary Science, 2021)
Klebsiella pneumoniae is an important pathogen that can infect both humans and cattle. The widespread Klebsiella pneumoniae and its high drug resistance make it difficult to treat Klebsiella infections/diseases. In this study, a lytic Klebsiella pneumoniae bacteriophage vB_Kpn_B01 was isolated from a dairy farm trough in Sichuan Province, and its biological properties were studied, and the entire genome of vB_Kpn_B01 was sequenced. The therapeutic effects of the phage on disease-causing mice were preliminarily tested. Phages found in this study are double-stranded DNA bacterial viruses belonging to the family Siphoviridae, Sugarlandvirus. The results suggest that vB_Kpn_B01 has strong specificity and low adaptability to different adverse conditions. Meanwhile, the predicted gene products of phage vB_Kpn_B01 comprised 149 coding sequences (CDS) and 25 tRNAs, of which 34 CDS had known functions. Of course, vB_Kpn_B01 did not contain any known antibiotic-resistant or virulent genes. The pathological sections of the liver and lungs of mice showed that the inflammatory scores of the treatment group were lower than in the bacterial group. Phage vB_Kpn_B01 alleviated the inflammatory response in the organs of the infected mice, and the organ tissue bacterial load of the treatment group was significantly lower than that of the bacterial group. Therefore, vB_Kpn_B01 can inhibit the proliferation of Klebsiella pneumoniae 18 in vivo and can alleviate the inflammation of target organs caused by infectious bacteria, which preliminarily indicates that vB_Kpn_B01 has a certain therapeutic effect on laboratory-infected mice.